Gudenus Cave : the earliest humans of Austria - Bednarik, Robert G. (Archaeopress Archaeology, 2022)
Summarising 60 years of research by the author at the earliest human occupation site known in Austria (1962 to 2021), this book describes the strategies and methods of studying a Pleistocene cave site that had been regarded as fully excavated, and their long-term applications.